A Prospective Comparison Study of Heart Rate Variability During Menses in Young Women With Dysmenorrhea. (July 2016) - Wang, Yu-Jen; Wang, Yi-Zen; Yeh, Mei-Ling
Background: Numerous studies have demonstrated autonomic abnormalities in various pain conditions. However, few have investigated heart rate variability (HRV) in young women with primary dysmenorrhea, and the conclusions have been inconsistent. More evidence is required to confirm the reported trend for consistent fluctuation of HRV parameters in dysmenorrhea. Purpose: The study's aim was to determine whether significant differences exist between young women with and without dysmenorrhea for heart rate (HR), blood pressure (BP), and HRV parameters during menses. Design: A prospective comparison design with repeated measures was used. Setting and participants: Sixty-six women aged 18–25 with dysmenorrhea and 54 eumenorrheic women were recruited from a university in northern Taiwan. Methods: High-frequency and low-frequency HRV parameters (HF and LF), LF/HF ratio, BP, and HR were measured daily between 8 p.m. and 10 p.m. from Day 1 to Day 6 during menses. The generalized estimating equation was used to analyze the effects of group, time, and Group × Time interaction on these variables. Results: HF values were significantly lower in the dysmenorrhea than in the eumenorrhea group, but there were no differences in BP, HR, LF, or LF/HF ratio. Conclusion: Reduced HF values reflect reduced parasympathetic activity and autonomic instability in young women with dysmenorrhea. Future longitudinal studies are warranted to examine autonomic regulation in menstrual pain of varying intensities associated with dysmenorrhea-related symptoms and to clarify the causal relationship between dysmenorrhea and HRV fluctuations.